Unclonable dynamic k-times anonymous authentication - Xin LIU; Qiu-liang XU (Tongxin xuebao)
In previous works of k-times anonymous authentication,two problems have not been properly solved:1)how to allow application providers to assign different maximal numbers of access for each user without weakened anonymity,and 2)how to protect against massive clone attacks mounted by malicious users.To overcome these obstacles,a revised scheme was proposed.It incorporated several crucial tools including the proof that a committed value is less than another committed value,dynamic accumulator,the method of cloning detection based on n-times show e-tokens,etc.The new scheme is proven secure in a new security model which was obtained by modifying the security model of Teranishi et al.Moreover,the registration protocol of the new scheme is concurrently-secure,so it is fit for the deployment in realistic asynchronous network setting(e.g.,Internet).